PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEBUGARAN JASMANI DI SMK KANSAI PEKANBARU - Rahmadani, Rahmadani; Sulastio, Agus; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Physical education is a learning process through useful activities toimprove a person's quality and train psychomotor skills to achieve the desired goals. In physical education there are several aspects, one of which is physical fitness. According to Wirnantika (2017) in Cristiana (2020), physical fitness activities can be carried out every day without experiencing significant fatigue, so that you still have the energy to carry out other activities. Cooperative Learning is a learning model developed to achieve learning outcomes in the form of academic achievement, tolerance, acceptance of diversity, and skill development.